Family sepsidae - Silva, Vera Cristina [UNESP] (Magnolia Press, 2016)
An updated Catalogue of the Sepsidae of Colombia is presented. This small acalyptratae family is poorly known in Colombia, with only ten reported species in four genera.
Keywords: Catalogue; Colombia; Diptera; Distribution; Neotropical region